KEANEKARAGAMAN DAN KELIMPAHAN JENIS TERIPANG DI PANTAI LANDU, PULAU LANDU, KABUPATEN ROTE NDAO - arnold christian hendrik; alefane ndun; Yanti Daud (Biology Department, Mathematics and natural science, Tadulako University, 2021)
Landu beach is a beach located on Landu Island, Southwest Rote District, Rote Ndao Regency, which is the southernmost district in Indonesia. Sea cucumbers are used by the coastal community of Landu Beach as food and sold to the market as a source of income. So far, it is not scientifically known the types of sea cucumbers and the level of sea cucumber diversity in the coastal waters of Landu. Therefore, this study aims to identify the diversity and abundance of sea cucumbers on Landu Beach, Landu Island, Rote Ndao Regency. This study used a survey method with the sampling technique using the quadratic transect method (quadrant transect method). With 5 transects, each transect consists of 5 plots. The data taken were in the form of sea cucumber species, the number of sea cucumbers per plot, and the state of the substrate per observation plot. The results of the study found 4 types of sea cucumber species in Landu Beach, namely Holothuria scabra, Holothuria arata, Holothuria leucospilota, and Bohadchia marmorata. The abundance of each type of sea cucumber found was Holothuria Scabra with the highest abundance value, namely 2.44 ind / m2 followed by Holothuria Arta (2.16ind / m2), Bohadchia Marmorata (1.92 ind / m2), and Holothuria Leucospilota (1.68 ind. / m2). Bohadchia Marmorata species has a frequency of 1.0 which means this species was found in the research plot seedlings. The next frequency values ​​are Holothuria Scabra (0.72), Holothuria Arta (0.68), and the lowest frequency value is Holothuria Leucospilota (0.60). For the diversity index value according to the Shannon-Wiener index (H ') ranges from 1.37 so it is categorized that Landu Beach has moderate diversity.